Implementasi Asuhan Gizi Berbasis Pangan Lokal sebagai Upaya Peningkatan Kognitif (Pengetahuan) Gizi Ibu yang memiliki Balita Stunting di Kepulauan Kabaena Timur - M, Habib Ihsan; Abadi, Ellyani (Universitas Batanghari Jambi, 2024)
The problem of stunting is one of the determinants of the quality of human resources because it has a fatal impact on increasing infant and child mortality rates. Stunting causes sufferers to get sick easily and have a body posture that is not optimal as an adult. Indirectly this is caused by a lack of knowledge of nutrition. Efforts to increase knowledge can be made by implementing a local food-based nutritional care program which is carried out by providing intensive counseling, accompanied by recommendations for local food menus and demonstrations of local food menus so that it can increase maternal nutritional knowledge. The purpose of this study was to determine changes in mother's nutritional knowledge before being given local food-based nutritional care. This type of research is a pre-experimental one group pre-test-post test design. The population was 30 toddlers aged 0-23 months who experienced stunting during the July period in the East Kabaena Islands and a sample of 27 people. The sampling technique uses simple random sampling. Knowledge data obtained using a questionnaire. The results of this research showed that from 27 samples the average knowledge score about nutrition was 5.2 and after implementing nutritional care the score was 10.2. The conclusion of this study is that local food-based nutrition care can improve maternal nutrition cognitive (knowledge).